Sites of high local frustration in DNA origami - Richard Kosinski (Nature Portfolio, 2019)
Self-assembly of DNA origami is a complex folding problem without a unified view of the energetic factors involved. Here the authors analyse identical structures that differ by nucleotide sequence and identify how mechanical stress at nucleation sites shapes the energy landscape.